Loss of oocytes due to conditional ablation of Murine double minute 2 (Mdm2) gene is p53‐dependent and results in female sterility. Issue 16 (18th July 2016) - Livera, Gabriel; Uzbekov, Rustem; Jarrier, Peggy; Fouchécourt, Sophie; Duquenne, Clotilde; Parent, Anne‐Simone; Marine, Jean‐Christophe; Monget, Philippe
Abstract : Murine double minute 2 and 4 (Mdm2, Mdm4) are major p53‐negative regulators, preventing thus uncontrolled apoptosis induction in numerous cell types, although their function in the female germ line has received little attention. In the present work, we have generated mice with specific invalidation of Mdm2 and Mdm4 genes in the mouse oocyte (Mdm2 Ocko and Mdm4 Ocko mice), to test their implication in survival of these germ cells. Most of the Mdm2 Ocko but not Mdm4 Ocko mice were sterile, with a dramatic reduction of the weight of ovaries and genital tract, a strong increase in follicle‐stimulating hormone and luteinizing hormone serum levels, and a reduction of anti‐mullerian hormone serum levels. Histological analyses revealed an obvious decrease of the number of growing follicles beyond the primary stage in Mdm2 Ocko ovaries in comparison to controls, with a pronounced increase in the apparition of primary atretic follicles, most being devoid of oocyte. Similar phenotypes were observed with Mdm2 Ocko Mdm4 Ocko ovaries, with no worsening of the phenotype. However, we failed to detect any increase in p53 level in mutant oocytes, nor any other apoptotic marker, introgression of this targeted invalidation in p53−/− mice restored the fertility of females. This study is the first to show that Mdm2, but not Mdm4, has a critical role in oocyte survival and would be involved in premature ovarian insufficiency phenotype. Abstract :